Karyotype analysis in some species of Consolida (Ranunculaceae) from Iran. Issue 4 (30th October 2013) - Tavassoli, Akhtar; Pakravan, Maneezheh; Kiarostami, Khadijeh; Poorhabibian, Roghayeh
Abstract: Consolida (dc .) S. F. Gray belongs to Ranunculaceae. The genus includes about 52 species worldwide. Here we report the diploid chromosome number and chromosome size and morphology for six Consolida species. For C. anthoroidea, C. leptocarpa, C. paradoxa and C. rugulosa the diploid chromosome number is reported for the first time. All investigated species have a diploid chromosome number of 2 n = 2 x = 16, except for C. persica having 2 n = 2 x = 14. The karyotypes of all six taxa are asymmetric, consisting of all four major chromosome types: metacentric, submetacentric, subtelocentric and telocentric chromosome type. However, considering the karyotype formula, all six species could be distinguished. In all taxa, metacentric chromosome pair 1 possesses a satellite. The only exception is C. rugulosa having an additional satellite positioned on metacentric chromosome pair 2. Karyotype data allow the separation of Aconitella from Consolida . Karyotype data plus morphological evidence support the reduction of C. paradoxa to formae level of C. rugulosa . (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)